Threat Construction for Dynamic Enemy Status in a Platformer Game using Classical Genetic Algorithm - Harisa, Ardiawan Bagus; Nugroho, Setiawan; Umaroh, Liya; Astuti, Yani Parti (Kinetik: Game Technology, Information System, Computer Network, Computing, Electronics, and Control, 2023)
Digital game genre such as Action-Platformer is widely popular among buyers on a platform like Steam. The non-playable character enemies in the game are important in action games. Unfortunately, they usually have static attributes like health points, damage, and enemy movement. Using the combination of procedural content generation and dynamic difficulty adjustment with a classical genetic algorithm, we drive the threat value of a platform to construct the enemy status, resulting in more dynamic enemies. We use the threat value as an input parameter calculated from the enemies’ stats in every platform, such as total damage that the enemy might produce, the player’s health point, and the enemy’s movement speed. We conclude that using a classical genetic algorithm may produce dynamic enemy status through the desired threat or danger set by the game designer as an input parameter. Moreover, the game designer may limit the generation with constraints.